The Influence Of Prices And Facilities On Tourists' Visiting Decisions At The Tjong A Fie Mansion Tourist Attraction - Anggreani, Christina; Kusriani, Onni (Jurnal Ilmu Sosial Mamangan, 2024)
Pricing plays an important role in tourists' visiting decisions. The prices set by the manager should adjust to the expectations of tourists who come to visit. Pricing by tourist attraction managers must of course be balanced with the completeness of the facilities offered to tourists. The purpose of this research was to find out whether there was an influence of prices and facilities on tourist visit decisions at Tjong A Fie Mansion period of November 2020. The method used in this study was a quantitative method with multiple linear regression analysis techniques. The data used were secondary data, hypothesis testing using the test of the coefficient of determination (R2), Simultaneous Test (F) and partial test (t) by calculation using the SPSS program and using slovin program. The sample of this study was 186 visitors. The results of simultaneous and partial showed that prices and facilities has positive and significantly influence on tourist visit decisions at Tjong A Fie Mansion.